Technology in sports and exercise: advantage for performance and athlete`s protection or increased risk for injury? - Brueggemann, G. P. (ISBS Proceedings Archive (Michigan), 2017)
This presentation describes the enormous development of technology and methodology in biomechanics of sports related to performance and sporting goods, apparatus and equipment. It will critically discuss the relevance and importance of technology for performance and it`s enhancement on one hand and the impact of human resources and training on the other hand. Technology of sporting goods and sport equipment is not only developed to enhance performance but also to decrease the risk of injury during sport activity and exercise. The effects of advanced technology will critically be reviewed regarding to their efficiency and sustainability to the athlete in elite and recreational sports and exercise.